# Taylor series Write out the first three nonzero terms of the Taylor series for the following functions centered at the given point a. Then write the series using summation notation. f(x)=cosh(2x-2),a=1

Taylor series Write out the first three nonzero terms of the Taylor series for the following functions centered at the given point a. Then write the series using summation notation.
$$\displaystyle{f{{\left({x}\right)}}}={\text{cosh}{{\left({2}{x}-{2}\right)}}},{a}={1}$$

• Questions are typically answered in as fast as 30 minutes

### Plainmath recommends

• Get a detailed answer even on the hardest topics.
• Ask an expert for a step-by-step guidance to learn to do it yourself.

sovienesY
We have to write first three nonzero terms of the taylor series for the function
$$\displaystyle{f{{\left({x}\right)}}}={\text{cosh}{{\left({2}{x}-{2}\right)}}},{a}={1}$$
$$\displaystyle{f{{\left({x}\right)}}}={\text{cosh}{{\left({2}{x}-{2}\right)}}},{f{{\left({1}\right)}}}={\text{cosh}{{\left({0}\right)}}}={1}$$
$$\displaystyle{f}'{\left({x}\right)}={2}{\text{sinh}{{\left({2}{x}-{2}\right)}}},{f}'{\left({1}\right)}={2}{\text{sinh}{{\left({0}\right)}}}={0}$$
$$\displaystyle{f}{''}{\left({x}\right)}={4}{\text{cosh}{{\left({2}{x}-{2}\right)}}},{f}{''}{\left({1}\right)}={4}{\text{cosh}{{\left({0}\right)}}}={4}$$
$$\displaystyle{f}{'''}{\left({x}\right)}={8}{\text{sinh}{{\left({2}{x}-{2}\right)}}},{f}{'''}{\left({1}\right)}={8}{\text{sinh}{{\left({0}\right)}}}={0}$$
$$\displaystyle{{f}^{{4}}{\left({x}\right)}}={16}{\text{cosh}{{\left({2}{x}-{2}\right)}}},{{f}^{{4}}{\left({1}\right)}}={16}{\text{cosh}{{\left({0}\right)}}}={16}$$
$$\displaystyle{{f}^{{5}}{\left({x}\right)}}={32}{\text{sinh}{{\left({2}{x}-{2}\right)}}},{{f}^{{5}}{\left({1}\right)}}={32}{\text{sinh}{{\left({0}\right)}}}={32}$$
$$\displaystyle{{f}^{{6}}{\left({x}\right)}}={64}{\text{cosh}{{\left({2}{x}-{2}\right)}}},{{f}^{{6}}{\left({1}\right)}}={64}{\text{cosh}{{\left({0}\right)}}}={64}$$
First term $$\displaystyle{f{{\left({1}\right)}}}={1}$$
Second term $$\displaystyle{f}'{\left({1}\right)}{\left({x}-{1}\right)}={0},{\left({x}-{1}\right)}={0}$$
Third term $$\displaystyle{\frac{{{f}{''}{\left({1}\right)}}}{{{2}!}}}{\left({x}-{1}\right)}^{{2}}={\frac{{{4}}}{{{2}!}}}{\left({x}-{1}\right)}^{{2}}={2}{\left({x}-{1}\right)}^{{2}}$$
Third term $$\displaystyle{\frac{{{f}{'''}{\left({1}\right)}}}{{{3}!}}}{\left({x}-{1}\right)}^{{3}}={\frac{{{0}}}{{{3}!}}}{\left({x}-{1}\right)}^{{3}}={0}$$
Fourth term $$\displaystyle{\frac{{{{f}^{{4}}{\left({1}\right)}}}}{{{4}!}}}{\left({x}-{1}\right)}^{{4}}={\frac{{{16}}}{{{4}!}}}{\left({x}-{1}\right)}^{{4}}={\frac{{{2}}}{{{3}}}}{\left({x}-{1}\right)}^{{4}}$$
Fifth term $$\displaystyle{\frac{{{{f}^{{5}}{\left({1}\right)}}}}{{{5}!}}}{\left({x}-{1}\right)}^{{5}}={\frac{{{0}}}{{{5}!}}}{\left({x}-{1}\right)}^{{5}}={0}$$
Sixth term $$\displaystyle{\frac{{{{f}^{{6}}{\left({1}\right)}}}}{{{6}!}}}{\left({x}-{1}\right)}^{{6}}={\frac{{{64}}}{{{6}!}}}{\left({x}-{1}\right)}^{{6}}$$
So, first three non-zero term of taylor series are
$$\displaystyle{1},{2}{\left({x}-{1}\right)}^{{2}},{\frac{{{2}}}{{{3}}}}{\left({x}-{1}\right)}^{{4}}$$
Now, we will write series summation notation
$$\displaystyle{f{{\left({x}\right)}}}={\sum_{{{n}={0}}}^{\infty}}{\frac{{{{f}^{{{\left({n}\right)}}}{\left({1}\right)}}}}{{{n}!}}}{\left({x}-{1}\right)}^{{n}}$$
$$\displaystyle={f{{\left({1}\right)}}}+{\frac{{{{f}^{{{\left({1}\right)}}}{\left({1}\right)}}}}{{{1}!}}}{\left({x}-{1}\right)}+{\frac{{{{f}^{{{\left({2}\right)}}}{\left({1}\right)}}}}{{{2}!}}}{\left({x}-{1}\right)}^{{2}}+{\frac{{{{f}^{{{\left({3}\right)}}}{\left({1}\right)}}}}{{{3}!}}}{\left({x}-{1}\right)}^{{3}}+{\frac{{{{f}^{{{\left({4}\right)}}}{\left({1}\right)}}}}{{{4}!}}}{\left({x}-{1}\right)}^{{4}}+{\frac{{{{f}^{{{\left({5}\right)}}}{\left({1}\right)}}}}{{{5}!}}}{\left({x}-{1}\right)}^{{5}}+{\frac{{{{f}^{{{\left({6}\right)}}}{\left({1}\right)}}}}{{{6}!}}}{\left({x}-{1}\right)}^{{6}}+\ldots$$
$$\displaystyle={1}+{0}+{\frac{{{4}}}{{{2}!}}}{\left({x}-{1}\right)}^{{2}}+{0}+{\frac{{{16}}}{{{4}!}}}{\left({x}-{1}\right)}^{{4}}+{0}+{\frac{{{64}}}{{{6}!}}}{\left({x}-{1}\right)}^{{6}}+\ldots$$
$$\displaystyle={1}+{\frac{{{4}}}{{{2}!}}}{\left({x}-{1}\right)}^{{2}}+{\frac{{{16}}}{{{4}!}}}{\left({x}-{1}\right)}^{{4}}+{\frac{{{64}}}{{{6}!}}}{\left({x}-{1}\right)}^{{6}}+\ldots$$
$$\displaystyle={\sum_{{{n}={0}}}^{\infty}}{\frac{{{2}^{{{2}{n}}}}}{{{\left({2}{n}\right)}!}}}{\left({x}-{1}\right)}^{{{2}{n}}}$$